2017
DOI: 10.3389/fgene.2017.00087
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Ashkenaz, Ashkenazic Jews, and Yiddish

Abstract: Recently, the geographical origins of Ashkenazic Jews (AJs) and their native language Yiddish were investigated by applying the Geographic Population Structure (GPS) to a cohort of exclusively Yiddish-speaking and multilingual AJs. GPS localized most AJs along major ancient trade routes in northeastern Turkey adjacent to primeval villages with names that resemble the word “Ashkenaz.” These findings were compatible with the hypothesis of an Irano-Turko-Slavic origin for AJs and a Slavic origin for Yiddish and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…It relies on extrapolating the genomic similarity between the query and reference populations to infer the likely biogeographical affinity of the former using the geographic locations (latitude and longitude) corresponding to the latter as a reference. GPS has been effectively employed for reconstructing the population history of several populations worldwide [ 2 , 6 , 7 , 9 11 ]. However, so far its utility and robustness in accurately localizing highly admixed populations whose genetic structure has been modified by significant demographic, biological and social factors has remained largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…It relies on extrapolating the genomic similarity between the query and reference populations to infer the likely biogeographical affinity of the former using the geographic locations (latitude and longitude) corresponding to the latter as a reference. GPS has been effectively employed for reconstructing the population history of several populations worldwide [ 2 , 6 , 7 , 9 11 ]. However, so far its utility and robustness in accurately localizing highly admixed populations whose genetic structure has been modified by significant demographic, biological and social factors has remained largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction of biogeographical origins is obtained by converting genomic information into geographical coordinates. All biogeographical inferences were carried out using the geographic population structure (GPS) tool, which matches the admixture proportions of a test individual with those of reference populations known to have resided in a certain geographical region for a substantial period of time ( Elhaik et al 2014 ; Das et al 2017 ). The efficacy of DREAM’s biogeographical predictions was assessed on 584 worldwide individuals from 33 countries ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…GPS then converts the genetic distances between that individual and the nearest M = 10 reference populations into geographic distances. The reference populations can be thought of as “pulling” the individual toward their location in a strength proportional to the similarity of their admixture components until a “consensus” is reached ( Das et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Their analyses (Mikheyev et al (2019) Figure 1A) shows that Ashkenazic Jews cluster with North Ossetia and Caucasus populations, rather than their neighboring communities. It is difficult to reconcile this finding with the authors' beliefs that the high genetic-geographic correlation makes their populations "strongly informative about the geographic origins of the Khazars" and their criticism towards past studies that showed a Caucasus origin for Ashkenazic Jews (Das et al 2016;Das et al 2017).…”
Section: Choice Of the Reference Datasetmentioning
confidence: 85%